CRYSTAL STRUCTURE OF FILATOVITE, K[(AL,ZN)2(AS,SI 2O8], THE FIRST ARSENATE OF THE FELDSPAR GROUP - Filatov S.K.; Krivovichev S.V.; Burns P.C.; Vergasova L.P. (My University, 2004)
The crystal structure of filatovite, K[(Al,Zn)2(As,Si 2O8] (monoclinic, I2/c, a = 8.772(1), b = 13.370(2, c = 14.690(2) Å, β = 115.944(6)°, V = 1549.1(4) Å3) has been solved by direct methods and refined to R1 = 0.033 on the basis of 1959 unique observed reflections with |Fo| ≥ 4σF. It is isotypic with the structures of celsian, Ba[Al2Si2O8], and its synthetic analogues. The structure contains four symmetry independent tetrahedral sites. The T(1) and T(4) sites have the same refined occupancy of As0.55Si0.45 and are characterized by average bond lengths of 1.634 Å. The occupancies of the T(2) and T(3) sites are Al0.94Zn0.06 and Al0.96Zn0.04, respectively, with average <T(2 -O> and <T(3)-O> bond lengths of 1.753 and 1.754 Å, respectively. Consistent with Al-Si ordering in celsian, (As,Si O4 tetrahedra are surrounded by (Al,Zn)O4 tetrahedra and vice versa. One symmetry independent K+ cation resides in framework cavities and is coordinated by nine O atoms with the average bond length of 3.02 Å. Incorporation of pentavalent T5+ cations into the feldspar-like tetrahedral framework is possible if it is accompanied by incorporation of T2+ and T3+ cations into adjacent tetrahedral sites.
Keywords: filatovite